CANVAS: A Cloud-based Research Data Analytics Environment and System - Kim, Seongchan; Song, Sa-kwang (韓國컴퓨터情報學會論文誌, 2021)
In this paper, we propose CANVAS (Creative ANalytics enVironment And System), an analytics system of the National Research Data Platform (DataON). CANVAS is a personalized analytics cloud service for researchers who need computing resources and tools for research data analysis. CANVAS is designed in consideration of scalability based on micro-services architecture and was built on top of open-source software such as eGovernment Standard framework (Spring framework), Kubernetes, and JupyterLab. The built system provides personalized analytics environments to multiple users, enabling high-speed and large-capacity analysis by utilizing high-performance cloud infrastructure (CPU/GPU). More specifically, modeling and processing data is possible in JupyterLab or GUI workflow environment. Since CANVAS shares data with DataON, the research data registered by users or downloaded data can be directly processed in the CANVAS. As a result, CANVAS enhances the convenience of data analysis for users in DataON and contributes to the sharing and utilization of research data. 이 논문에서 우리는 국가연구데이터플랫폼 (DataON)의 분석서비스인 CANVAS (Creative ANalytics enVironment And System)를 제안한다. CANVAS는 연구데이터 분석 자원과 도구가 필요한 연구자들을 위한 개인화된 분석 클라우드 서비스이다. CANVAS는 마이크로서비스 아키텍쳐 기반으로 확장성을 고려하여 설계하였으며 전자정부프레임워크인 Spring 프레임워크, Kubernetes, JupyterLab 등의 오픈소스 소프트웨어를 이용하여 구축하였다. 구축된 시스템은 여러 사용자에게 개인화된 분석환경을 제공하며 고성능 클라우드 인프라 (CPU·GPU)를 활용하여 고속의 대용량 데이터 분석이 가능하다. 구체적으로 JupyterLab 이나 GUI 워크플로우 환경에서 데이터 모델링 및 처리가 가능하다. CANVAS는 DataON과 데이터가 공유되므로 사용자가 등록하거나 다운로드 받은 연구데이터는 CANVAS에서 바로 분석을 수행할 수 있다. 이로서 CANVAS는 DataON 사용자의 데이터 분석 편의성을 높이고 연구데이터 공유·활용 활성화에 기여한다.